Comprehensive and transformative learning in school evaluation - Iafrancesco Villegas, Giovanni (2017)
This article new concepts are proposed assessment from the perspective of the proposals " Education, School Education and Transformative -EEPT- new evaluation objectives are formulated in the areas of conceptual, procedural, cognitive and behavioral domains, accompanied 10 principles that facilitate characterize the proposal and recommended evaluative and describe new approaches, types and models of comprehensive evaluation and learning.